Microstructure and Corrosion Properties of Modified Low Carbon Martensitic Stainless Alloys Deposited by Laser Metal Deposition - Du Toit, Madeleine (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2018.